Pretreatment with Hydroxyurea of the Patient with Essential Thrombocythemia Followed by Coronary Artery Bypass Surgery - Ziadinov, Edem (OMJ, 2014)
The risk of thrombosis is high in patients with essential thrombocythemia. Special precaution needed for those patients who will undergo Coronary artery bypass grafting. We are reporting a 62 years old patient with ischemic heart disease who was found to have essential thrombocythemia. This report explains the preoperative management and the postoperative risks anticipated due to the treatment.